Untargeted LC-MS metabolomics reveals the metabolic responses in olive flounder subjected to hirame rhabdovirus infection - Gu, Bingyu; Pan, Fenghuang; Wang, Hongxiang; Zou, Zhiyi; Song, Junya; Xing, Jing; Tang, Xiaoqian; Zhan, Yuanchao (Frontiers in Immunology, 2023)
Hirame novirhabdovirus (HIRRV), which mainly infects the olive flounder (Paralichthys olivaceus), is considered to be one of the most serious viral pathogens threatening the global fish culture industry. However, little is known about the mechanism of host-pathogen interactions at the metabolomic level. In this study, in order to explore the metabolic response of olive flounder to HIRRV infection, liquid chromatography mass spectrometry (LC-MS) was used to detect the changes of endogenous compounds of the olive flounder after HIRRV infection. A total of 954 unique masses were obtained, including 495 metabolites and 459 lipids. Among them, 7 and 173 qualified differential metabolites were identified at 2 days and 7 days post-infection, respectively. Distinct metabolic profiles were observed along with viral infection. At the early stage of infection, only a few metabolites were perturbed. Among them, the level of inosine and carnosine were increased and the potential antiviral ability of these two metabolites was futher comfirmed by exogenous addition experiment. At the late stage of HIRRV infection, the metabolic profiles changed remarkably. The changes in amino acids and nucleotides especially the 7-methylguanine also accelerated the amplification of viral particles. And the down-regulation of glutathione (GSH) implied an elevated level of ROS (reactive oxygen species) that attenuated the immune system of flounders. HIRRV also induced the accumulation of purine and reduction of pyrimidine, and elevated LPC and LPE levels. The unbalanced purine/pyrimidine and altered lipid profile may be beneficial for the replication and infection of HIRRV at the late stage of infection. These findings provide new insights into the pathogenic mechanism of HIRRV infection in olive flounder.